2004
DOI: 10.1063/1.1688433
|View full text |Cite
|
Sign up to set email alerts
|

The Günther’s formalism in classical field theory: momentum map and reduction

Abstract: The polysymplectic formalism in local field theory, developed by Günther [J. Diff. Geom. 25, 23 (1987)], is revised. A new approach and new results on momentum maps and reduction are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 21 publications
0
97
0
2
Order By: Relevance
“…Initiated by C. Gunther [12] and [13] based on n-symplectic model [14,15], it has been shown that the symplectic structure on the phase space remains true, if we replace the symplectic form by a vector valued form, that is called polysymplectic. This extension defines an action of G over…”
Section: R M a H Rmentioning
confidence: 99%
“…Initiated by C. Gunther [12] and [13] based on n-symplectic model [14,15], it has been shown that the symplectic structure on the phase space remains true, if we replace the symplectic form by a vector valued form, that is called polysymplectic. This extension defines an action of G over…”
Section: R M a H Rmentioning
confidence: 99%
“…Concerning reduction theory in general, only partial results about reduction by foliations are currently being studied [49]. The corresponding reduction theorem has been stated and proved for the k-symplectic formulation [84], but the theory of reduction of multisymplectic Lagrangian and Hamiltonian systems under the action of groups of symmetries is still under research, and only partial results have been achieved [17,18,19,81].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…For instance, we have the so-called k-symplectic formalism which uses the k-symplectic forms introduced by Awane [4,5,6], and which coincides with the polysymplectic formalism described by Günther [46] (see also [84]). A natural extension of this is the k-cosymplectic formalism, which is the generalization to field theories of the cosymplectic description of non-autonomous mechanical systems [75,76].…”
Section: Introductionmentioning
confidence: 99%
“…First, several Hamiltonian models can be stated, and the equivalence among them is not always clear (see, for instance, [2], [12], [19], [21], [22], [23], [40], [43]). Furthermore, there are equivalent Lagrangian models with non-equivalent Hamiltonian descriptions [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%